2014
DOI: 10.1371/journal.pone.0114196
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-Acetic Acid-Producing Yeasts in the Phyllosphere of the Carnivorous Plant Drosera indica L

Abstract: Yeasts are widely distributed in nature and exist in association with other microorganisms as normal inhabitants of soil, vegetation, and aqueous environments. In this study, 12 yeast strains were enriched and isolated from leaf samples of the carnivorous plant Drosera indica L., which is currently threatened because of restricted habitats and use in herbal industries. According to similarities in large subunit and small subunit ribosomal RNA gene sequences, we identified 2 yeast species in 2 genera of the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 75 publications
8
85
1
7
Order By: Relevance
“…In addition, our previous study supports that IAA production is influenced by the pH value of the medium. 26 We observed that 6 of 12 tested yeast isolates produced low levels of IAA, 5 isolates produced similar levels of IAA, and one isolate produced high levels of IAA in an acidic environment than in a nearly neutral environment. All of the isolates could not produce IAA in an alkaline environment (pH 9).…”
Section: Iaa Biosynthetic Pathwaysmentioning
confidence: 71%
See 4 more Smart Citations
“…In addition, our previous study supports that IAA production is influenced by the pH value of the medium. 26 We observed that 6 of 12 tested yeast isolates produced low levels of IAA, 5 isolates produced similar levels of IAA, and one isolate produced high levels of IAA in an acidic environment than in a nearly neutral environment. All of the isolates could not produce IAA in an alkaline environment (pH 9).…”
Section: Iaa Biosynthetic Pathwaysmentioning
confidence: 71%
“…26 The tested yeast strains were collected from leaf samples of the carnivorous plant Drosera indica L. We found that the growth of Ustilago esculenta was not influenced by any tested IAA concentration and that a high IAA concentration (5,000 mM) significantly inhibited the growth of 11 of 12 plant-associated yeasts. In the phylum Ascomycota, low concentrations of exogenous IAA (312.5-625 mM) promoted or did not influence yeast growth.…”
Section: Iaa In Fungal -Fungal Interactionsmentioning
confidence: 79%
See 3 more Smart Citations